Policy Implementation Performance of Primary School Leaders in Malaysia: An Exploratory Factor Analysis - Noryati, Alias; Zainudin, Awang (2019)
The aim of this study is to develop a scale for assessing the policy implementation performance of public primary school leaders in Malaysia. The “Implementation Leadership Scale (ILS)” by Aarons, Ehrhart and Farahnak (2014) and part of the “Teacher’s Competency Scale” by Ghafar (2015) were adapted and customised to suit the context of the study in measuring school leaders' policy implementation performance. The respondents were 228 senior primary school leaders who included headmasters and senior teacher assistants in three categories: academic, student affairs, and co-curriculum. Clustered random sampling was used to select the respondents. Results of the exploratory factor analysis (EFA) revealed six underlying components of policy implementation performance with 38 indicators, the first four of which are proactive, knowledgeable, supportive, and perseverance implementation leadership. The last two components are ability to perform and standard of performance. Evidently, the six components explained 65.1% of the total variance. The reliability of the policy implementation performance construct was 0.95, while that of other constructs ranges from 0.79 to 0.89. In addition to contributing further insight to the current literature on policy implementation performance, the results also provide a reliable source of information to researchers and professional practitioners of educational policies for future research in policy implementation performance.